Narrative of a voyage to the Pacific and Beering's Strait, to co-operate with the polar expeditions [electronic resource] : performed in His Majesty's ship Blossom, under the command of Captain F.W. Beechey, R. N., F.R.S. &c. in the years 1825, 26, 27, 28. - Beechey, F. W. (Frederick William), 1796-1856 (Philadelphia : Carey & Lea, 1832)
"Published by authority of the Lord's Commissioners of the Admiralty." Electronic reproduction. Mode of access: Internet. 44